Aircraft routing with minimal climate impact: The REACT4C climate cost function modelling approach (V1.0) - Grewe, Volker; Frömming, Christine; Matthes, Sigrun; Brinkop, Sabine; Ponater, Michael; Dietmüller, Simone; Jöckel, Patrick; Garny, Hella; Tsati, Eleni; Dahlmann, Katrin; Sovde, O.A.; Fuglestvedt, J.S.; et al. (Geoscientific Model Development, 2014)
In addition to CO2, the climate impact of aviation is strongly influenced by non-CO2 emissions, such as nitrogen oxides, influencing ozone and methane, and water vapour, which can lead to the formation of persistent contrails in ice supersaturated regions. Because these non-CO2 emission effects are characterised by a short lifetime, their climate impact largely depends on emission location and time, i.e. emissions in certain locations (or times) can lead to a greater climate impact (even on the global average) than the same emission in other locations (or times). Avoiding these climate sensitive regions might thus be beneficial to climate. Here, we describe a modelling chain for investigating this climate impact mitigation option. It forms a multi-step modelling approach, starting with the simulation of the fate of emissions released at a certain location and time (time-region grid points). This is performed with the chemistry–climate model EMAC, extended by the two submodels AIRTRAC (V1.0) and CONTRAIL (V1.0), which describe the contribution of emissions to the composition of the atmosphere and to contrail formation, respectively. The impact of emissions from the large number of time-region grid points is efficiently calculated by applying a Lagrangian scheme. EMAC also includes the calculation of radiative impacts, which are, in a second step, the input to climate metric formulas describing the global climate impact of the mission at each time-region grid point. The result of the modelling chain comprises a four dimensional dataset in space and time, which we call climate cost functions, and which describe at each grid point and each point in time, the global climate impact of an emission. In a third step, these climate cost functions are used in an air traffic simulator (SAAM), coupled to an emission tool (AEM) to optimise aircraft trajectories for the North Atlantic region. Here, we describe the details of this new modelling approach and show some example results. A number of sensitivity analyses are ...